A novel synthesis of (2S)-3-(2, 4, 5-trifluorophenyl)propane-1, 2-diol by sharpless asymmetric epoxidation method. Issue 6 (19th March 2019) - Anil, Derya; Altundas, Ramazan; Kara, Yunus
Abstract: Synthesis of (2 S )-3-(2, 4, 5-trifluorophenyl)propane-1, 2-diol by the Sharpless asymmetric epoxidation reaction has been achieved. 2, 4, 5-Trifluorobenzaldehyde with methyl 2-(triphenyl-λ 5 -phosphanylidene)acetate gave methyl ( E )-3-(2, 4, 5-trifluorophenyl)acrylate in 83% yield. The reduction of ester group with DibalH followed by Sharpless asymmetric epoxidation gave ((2 R, 3 R )-3-(2, 4, 5-trifluorophenyl)oxiran-2-yl)methanol. Pd/C-catalyzed hydrogenation of epoxy alcohol furnished (2 S )-3-(2, 4, 5-trifluorophenyl)propane-1, 2-diol with >90% ee and 71% yield. Graphical Abstract: